2020
DOI: 10.1007/s00277-020-04221-0
|View full text |Cite
|
Sign up to set email alerts
|

Concepts in immuno-oncology: tackling B cell malignancies with CD19-directed bispecific T cell engager therapies

Abstract: The B cell surface antigen CD19 is a target for treating B cell malignancies, such as B cell precursor acute lymphoblastic leukemia and B cell non-Hodgkin lymphoma. The BiTE® immuno-oncology platform includes blinatumomab, which is approved for relapsed/refractory B cell precursor acute lymphoblastic leukemia and B cell precursor acute lymphoblastic leukemia with minimal residual disease. Blinatumomab is also being evaluated in combination with other agents (tyrosine kinase inhibitors, checkpoint inhibitors, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 92 publications
0
30
0
9
Order By: Relevance
“…In recent years, the application of immunotherapy has become one of the most promising methods of treating haematological malignancies. 1,2 The clinical implementation of therapy directed against the specific B-cell marker CD19 has helped to improve outcomes in patients with relapsed/ refractory (R/R) B-lineage acute lymphoblastic leukaemia (ALL) [3][4][5][6] as well as ALL with a long persistence of leukaemic cells in the bone marrow (BM). 7,8 CD19 is highly expressed on the surface of leukaemic cells in nearly all B-cell malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the application of immunotherapy has become one of the most promising methods of treating haematological malignancies. 1,2 The clinical implementation of therapy directed against the specific B-cell marker CD19 has helped to improve outcomes in patients with relapsed/ refractory (R/R) B-lineage acute lymphoblastic leukaemia (ALL) [3][4][5][6] as well as ALL with a long persistence of leukaemic cells in the bone marrow (BM). 7,8 CD19 is highly expressed on the surface of leukaemic cells in nearly all B-cell malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…These mutations abolish the binding to Fcγ receptors and to complement component C1q while maintaining neonatal Fc receptor (FcRn) binding, enabling a stable IgG-like PK in vivo with an half-life of around 10 days in NSG mice. This feature is a major differentiation from Blinatumomab, a Tcell bispecific (TCB) antibody targeting CD19 and CD3ε approved in relapsed/refractory Bcell acute lymphoblastic leukemia, which have instead short half-life in vivo of 1-2 hours [7,9] CD20-TCB can redirect the activity of conventional CD4 and CD8 T cells against lymphoma cells by concomitant binding of CD20 on tumor cells and CD3 on T cells (S1b Fig) [7,10]. Previous studies revealed that CD20-TCB has a long half-life and induces selective activation of conventional T cells, resulting in efficient tumor regression of the aggressive DLBCL xenograft model WSU DLCL2 in preclinical animal models in human stem cell humanized (HSC) NSG mice [7].…”
Section: Introductionmentioning
confidence: 99%
“…Targeting the pan‐B‐lymphocyte antigen CD19 with the bispecific T‐cell engager blinatumomab is one of the modern ways of treating acute lymphocytic B‐cell precursor leukaemia (BCP‐ALL) 1,2 . This drug has been very successful in treating patients with relapsed/refractory (R/R) disease, 3,4 but it has recently been shown that blinatumomab is also effective in eradicating minimal residual disease (MRD) in patients with relapsed or primary BCP‐ALL 5,6 .…”
Section: Figurementioning
confidence: 99%